Measuring Readiness of ERP Application Implementation Using The Balanced Scorecard Method - verri Kuswanto; Riki Riki; Wiyono Hermanto (bit-Tech, 2021)
The paper entitled "Measuring Readiness Of ERP Application Implementation Using The Balanced Scorecard Method". The author takes the title as the background of the increasing number of companies that have started implementing the government's proposal, namely Industry 4.0, where each company is required to have an integrated system in making financial reports for internal and external purposes, many companies carry out Governance by re-implementing the system. The preparation process in implementing an integrated system is very important, because the implementation process is quite long and also the cost is not small, therefore we need a method that functions to provide a measurement in the form of a value or score to assist management in making appropriate and appropriate decisions. This preparation process is mature and the implementation process can be successful as expected. The Balanced Scorecard method prioritizes 4 perspectives, namely: financial perspective, customer perspective, internal business process perspective, learning and growth perspective. However, the perspective to be measured is the perspective of internal business processes and the perspective of learning growth. From this research, the results achieved are suggestions in determining planning which will be continued into an ERP application information system project management